The Imperial Theotokos: Revealing the Concept of Early Christian Imagery in Santa Maria Maggiore in Rome - Lidova, Maria (Convivium, 2015)
Abstract The paper is devoted to the Early Christian mosaic decoration of Santa Maria Maggiore church in Rome and focuses on the image of the Virgin and its role within the general program. The four surviving representations depict Mary in rich princely garb, notably an ornamented, golden dalmatica and jeweled headdress. With this elegant attire, these images strongly resemble those of empresses and other high-ranking women of the time and are often seen to be predecessors of later iconographic type, the Maria Regina. While this representation could have been determined by notions formulated by contemporary theologians about the figure of the Theotokos, it could also be the result of the earliest development of Marian iconography. In this paper the exact meaning of the image of the Virgin and of its female counterpart seated on the other side of Christ’s throne in the enigmatic composition of the Adoration of the Magi is considered to be of secondary importance to the very fact that both figures visually function within Late Antique associative techniques and perform the role of allegories. This multiple role and possible readings of the figure of Mary are further explored through comparison with intentional parallels of the Virgin’s image and several protagonists of the Old Testament cycle depicted in the Early Christian Sta Maria Maggiore mosaics.